Characteristics and Electronic Band Alignment of a Transparent p-CuI/n-SiZnSnO Heterojunction Diode with a High Rectification Ratio - Jeong Hyuk Lee; Byeong Hyeon Lee; Jeonghun Kang; Mangesh Diware; Kiseok Jeon; Chaehwan Jeong; Sang Yeol Lee; Kee Hoon Kim (Nanomaterials, 2021)
Transparent p-CuI/n-SiZnSnO (SZTO) heterojunction diodes are successfully fabricated by thermal evaporation of a (111) oriented p-CuI polycrystalline film on top of an amorphous n-SZTO film grown by the RF magnetron sputtering method. A nitrogen annealing process reduces ionized impurity scattering dominantly incurred by Cu vacancy and structural defects at the grain boundaries in the CuI film to result in improved diode performance; the current rectification ratio estimated at ±2 V is enhanced from ≈106 to ≈107. Various diode parameters, including ideality factor, reverse saturation current, offset current, series resistance, and parallel resistance, are estimated based on the Shockley diode equation. An energy band diagram exhibiting the type-II band alignment is proposed to explain the diode characteristics. The present p-CuI/n-SZTO diode can be a promising building block for constructing useful optoelectronic components such as a light-emitting diode and a UV photodetector.